2004
DOI: 10.1634/stemcells.2004-0023
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Telomerase Extends the Lifespan and Enhances Osteogenic Differentiation of Adipose Tissue–Derived Stromal Cells

Abstract: Expression of TERT, the catalytic protein subunit of the telomerase complex, can be used to generate cell lines that expand indefinitely and retain multilineage potential. We have created immortal adipose stromal cell lines (ATSCs) by stably transducing nonhuman primate-derived ATSCs with a retroviral vector expressing TERT. Transduced cells (ATSC-TERT) had an increased level of telomerase activity and increased mean telomere length in the absence of malignant cellular transformation. Long-term culture of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 35 publications
(50 reference statements)
2
39
0
Order By: Relevance
“…We show that the capacity to differentiate into the adipogenic and osteogenic lineage was maintained in iMSC#3 after immortalization, which is in line with previous studies [14][15][16][17]. In addition, a genome-wide profiling of mRNAs during adipogenesis, followed by IPA showed that numerous highly relevant biological processes were affected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We show that the capacity to differentiate into the adipogenic and osteogenic lineage was maintained in iMSC#3 after immortalization, which is in line with previous studies [14][15][16][17]. In addition, a genome-wide profiling of mRNAs during adipogenesis, followed by IPA showed that numerous highly relevant biological processes were affected.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have also demonstrated that long-term culturing of hMSCs affects their capacity to proliferate and differentiate, limiting their use in therapeutic applications and basic research. Immortalization can be achieved by several methods, including introduction of telomerase reverse transcriptase (TERT), human papillomavirus-16 E6 and E7 genes or simian virus 40 large antigen [14][15][16][17][18]. Previous studies have demonstrated that the phenotype of hMSCs is maintained after immortalization [19][20][21] and their differentiation potential has even been reported to improve thereafter [21].…”
mentioning
confidence: 99%
“…This needs elucidation since CS fragments have well reported biological activity both in vitro and in vivo. 38,39 Nevertheless, our results showed that the effect of PPy coating on hASC response was as strong with and without ES, suggesting that the surface chemistry of PPy plays a more important role in triggering cell response than in the electrical conductivity of PPy.…”
Section: Effect Of Polypyrrole-coated Polylactide Scaffolds On Adiposmentioning
confidence: 65%
“…The results were compared to a rhesus adult bone marrow stromal cell line (BMSC) and the rhesus ATSC stromal adult stem line, as well as an immortalized version of the ATSC line created by transfection with a retroviral vector resulting in the expression of telomerase activity (ATSC-TERT) (Kang et al, 2004). The common deletion was detected, but not quantified, in the in vivo-derived R4 cell line and the three ORMES cell lines derived from IVF-derived embryos.…”
Section: Mitochondrial Mutations In Oocytes Embryos and Stem Cellsmentioning
confidence: 99%